2020
DOI: 10.1088/1757-899x/959/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Complex (PEC) film based on chitosan as potential edible films and their antibacterial activity test

Abstract: The synthesis of polyelectrolyte complexes (PEC) based on chitosan and determination of their antibacterial properties had been conducted. The microstructure of PECs obtained were described by SEM analysis, while inhibition activity of PECs against S. aureus and E. coli was determined by measuring inhibitory zone diameter. Characteristics of chitosan, alginate and κ-carrageenan as natural polymers which non-toxic, biodagradable and safe to eat meet the edible film criteria. Chitosan as a polycationic interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Therefore, we hypothesized that the increased antibacterial effect of Chit30/AF-Pect (5 : 1) sponges compared to original polymers may be due to the formation of Schiff bases with imine groups (─RC═N─) from the interaction between chitosan's amino groups and oxidized pectin's aldehyde groups that enhances the positive charge of chitosan [85,86]. Similar results were reported for interpolyelectrolyte complexes of poly(acrylic acid)-chitosan [87], chitosan-alginate, chitosan-κ-carrageenan [88], and chitosan-oxidized pectin [51]. These polyelectrolyte complexes exhibited higher antibacterial activity against P. aeruginosa, P. oleovorans, and E. coli, S. aureus, and B. subtilis and S. aureus, respectively, than the original chitosan.…”
Section: Resultssupporting
confidence: 58%
“…Therefore, we hypothesized that the increased antibacterial effect of Chit30/AF-Pect (5 : 1) sponges compared to original polymers may be due to the formation of Schiff bases with imine groups (─RC═N─) from the interaction between chitosan's amino groups and oxidized pectin's aldehyde groups that enhances the positive charge of chitosan [85,86]. Similar results were reported for interpolyelectrolyte complexes of poly(acrylic acid)-chitosan [87], chitosan-alginate, chitosan-κ-carrageenan [88], and chitosan-oxidized pectin [51]. These polyelectrolyte complexes exhibited higher antibacterial activity against P. aeruginosa, P. oleovorans, and E. coli, S. aureus, and B. subtilis and S. aureus, respectively, than the original chitosan.…”
Section: Resultssupporting
confidence: 58%
“…Because of the electrostatic attraction between the polycationic chitosan and the polyanionic polysaccharides, it is possible to form polyelectrolyte complexes. Generally, it has been found that polyelectrolyte complexes (PEC) have better physico-mechanical properties than its constituent polymers due to its tighter microstructure [ 136 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEC have the ability to be used in matrices, beads, microparticle and nanoparticle systems, and microspheres and can be used as film coating [ 136 , 137 ], being used in drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%